Prevalence and Determinants of Hypertension and Obesity: A Rural-Urban Comparative Study in Telangana, India - L Murali; R Bhavani; Kavitha Y; Fathima Shoukath Ali (Perspectives In Medical Research)
Introduction: Non-communicable diseases (NCD) causes 74% of all deaths occurring worldwide. It is common among all age groups. The main behavioural risk factors included inadequate physical activity, tobacco usage, excessive consumption of alcohol and unhealthy diet. This study aimed for the comparison of risk factors for NCD in rural and urban areas and to determine the factors associated with hypertension and obesity. Methodology: This cross sectional study was done in the Rural and Urban field practice area of KMC. 300 adults (150 rural and 150 urban) were chosen through systematic sampling technique. WHO Steps questionnaire was used for the data collection. The data collected was analysed using SPSS. Chi square test was used as the statistical tests of significance. Results: The proportion of current tobacco users were 24.7% and 16% and current alcohol users were 56% and 46% in rural and urban respectively. Diet were inadequate and poor in both. Physical inactivity was 90.7% in urban, 52% in rural. Prevalence of Hypertension was 14% and 6%, obesity was 37.3% and 48.7% in rural and urban respectively. Diet was significantly associated with Hypertension and alcohol consumption was significantly associated with obesity in both. Conclusions: Both the rural and urban areas had high prevalence of risk factors. Smoking, alcohol consumption and hypertension were higher in rural area whereas physically inactivity and obesity were higher in urban area. Hence appropriate health education regarding NCDs and their risk factors are mandatory.